Differences in Anthropometric Characteristics and Body Composition of Water Polo Players in the 2019 World Junior Championship - Ivan Vasiljevic; Marko Aleksandrovic; Marin Corluka; Eldin Jeleskovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
This research aimed to determine the differences between the junior (U20) water polo players of national teams of Montenegro, and Australia regarding their anthropometric characteristics and body composition. The first sub-sample of the subjects consisted of 18 water polo players of the Montenegrin national team, who occupied the sixth position on the FINA World Men's Junior Water Polo Championship in Kuwait 2019. The second sub-sample consisted of 13 water polo players of the Australian national team, who occupied the eleventh position on the championship. The players were tested at the final preparations just before the World Championship. Anthropometric characteristics were evaluated using a battery of eight tests: body height, body weight, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold, upper-leg skinfold, lower leg skinfold; body composition was evaluated using a battery of three tests: body mass index, fat percentage, and muscle mass. The results of the t-test revealed that the water polo players of the two national teams do not have statistically significant differences in the variables. The results obtained in this research showed average team values for the estimated variables of water polo players of the two national teams (U20) who participated in the World Championship. That can serve as possible model parameters for all teams who want to participate in the U20 water polo World Championship. Differences in classification among water polo players may be related to the motor abilities, as well as technical and tactical parameters, as their anthropometric parameters were found to be similar.